2009
DOI: 10.1007/978-3-642-03658-3_6
|View full text |Cite
|
Sign up to set email alerts
|

Human Perception of Near-Duplicate Videos

Abstract: Abstract. Popular content in video sharing websites (e.g., YouTube) contains many duplicates. Most scholars define near-duplicate video clips (NDVC) as identical videos with variations on non-semantic features (e.g., image/audio quality), while a few others also include semantic features (different videos of similar content). However, it is unclear what exact features contribute to human perception of similar videos. In this paper, we present the results of a user study conducted with 217 users of video sharin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…They study the different definitions of nearduplicates and show that some near-duplicates that add visual content to the original video are not perceived as nearduplicates by users. In another work [25], the same authors conducted a study with 217 users of video sharing websites and reported that participants had a preference for one video when compared to its duplicates. Additionally, their study revealed that users were more tolerant to changes in the audio than in the video channel.…”
Section: Related Workmentioning
confidence: 99%
“…They study the different definitions of nearduplicates and show that some near-duplicates that add visual content to the original video are not perceived as nearduplicates by users. In another work [25], the same authors conducted a study with 217 users of video sharing websites and reported that participants had a preference for one video when compared to its duplicates. Additionally, their study revealed that users were more tolerant to changes in the audio than in the video channel.…”
Section: Related Workmentioning
confidence: 99%